Arabic Language Lecturers' Awareness of the Future Educational Framework 2030 - Attaqi, Khonsa Fillah; Nadhifah, Naura; Fajri, Adelia Nurul; Syarofah, Alfiatus (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v9i1.3145, 2024)
This study aims to find out how the Future Education Framework 2030 (FEF) was designed by the OECD, to find out how aware Arabic language lecturers are of the Future Education Framework 2030 (FEF) project in implementing Arabic language learning. This study uses qualitative method. Data collection was carried out through documentation studies, interviews, and observations. This study was conducted on Arabic language lecturers at UIN Malang. The results of the study show that there are 7 indicators set by the OECD in the implementation of the Future Education Framework 2030, including 1) Core foundations, 2) Transformative competencies, 2) Student Agency, 4) Knowledge for 2030, 5) Skills for 2030, 6) Attitude and Values ​​for 2030, 7) Anticipation-Action-Reflection competency development role. There are 7 skills possessed by lecturers in implementing the Future Education Framework 2030 project. 1) Technology skills, the lectures have the technology skills by teaching via zoom, e-learning, and making the interactive presentation in Arabic Teaching  2) Collaboration skills, the lectures do the collaborative research with students, and guide the collaboration event project 3) Communication skills, the lectures have a good communication skills that they can resolve conflicts and mediate problems with students  4) Time management skills, the lectures manage time of Arabic learning by making RPS and have a discipline time for learning 5) Research skills, the lectures actively having a research collaborate with students or lectures to improve the education 6) Teaching skills, the lecturers had modern pedagogical skills that had been applied to students and 7) Adaptation skills, lecturers are able to see into the future regarding the relevance of the material taught to the world of work when students have completed their education. Arabic language lecturers show that Arabic language lecturers have an awareness of the implementation of the Future Education Framework 2030 project.